Understanding amblyopia from the perspective of neurovascular units: changes in the retina and brain - Zhang, Lin; Zhao, Yaqi; Shi, Xiaolu; Wu, Fan; Shen, Yi (Frontiers in Cell and Developmental Biology, 2025)
As a developmental vision disorder, amblyopia has traditionally been studied with a focus on neurons. However, the neurovascular unit (NVU), a dynamic functional complex of neurons, blood vessels, and glial cells, has recently been implicated in amblyopia. This review systematically discusses the pathological changes and functional interactions of the NVU in retina and brain in amblyopia patients and experimental models, providing a new perspective for clinical intervention.